Use of active methodologies in promoting self-care and therapeutic adherence with users of a psychosocial care center (Research, Society and Development, 2021)
Mental disorders have different etiology, being characterized by the clinical manifestations that each individual will express. Worldwide, they have a major impact on the health scenario, it is estimated that 12% of the global disease burden is directly linked to these pathologies. Based on the above, the objective of this study was to report an experience of nursing students that took place in a psychosocial care center for alcohol and other drugs (CAPS AD, abbreviation in portuguese) in the metropolitan region of Belém-PA, which occurred through the implementation of playful actions on the site, which aimed at promoting adherence and continuity therapy. The present study is classified as descriptive, with a qualitative approach, of the experience report type, in which it seeks to understand the relationships developed based on different contexts. It was based on the methodology of problematizing the Arch of Charles Maguerez. As a result, it was demonstrated the indispensability of working with alternative methodologies with users, since this public, for the most part, does not have family support and as a result of abandonment, they end up choosing to live on the streets, at risk, as well as being more susceptible to abandoning the treatment offered at CAPS AD. Therefore, it is of great value to make it clear how much health education actions with less formal interactions with the use of active methodologies are important in the contribution of users' self-care, as well as in the learning of academics.